Krawtchouk Moment Invariant and Gaussian ARTMAP Neural Network: a combination techniques for image classification - Shahrul Nizam, Yaakob; Puteh, Saad (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 15th June 2006 at DKG 4 & DKG 5, Kubang Gajah, Arau, Perlis.